2022
DOI: 10.1039/d1ta10122f
|View full text |Cite
|
Sign up to set email alerts
|

Chaotropic anion based “water-in-salt” electrolyte realizes a high voltage Zn–graphite dual-ion battery

Abstract: Aqueous Zn-based batteries are promising candidates for grid energy storage due to their low cost, intrinsic safety, and environmental friendliness. Nevertheless, they suffer from limited energy density due to the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(33 citation statements)
references
References 61 publications
1
31
0
Order By: Relevance
“…[27][28][29] Table 1 shows the reported electrolyte designs to improve the narrow ESW of aqueous electrolytes. [30][31][32][33][34][35][36][37][38][39][40][41] Herein, we discuss strategies to suppress water decomposition for the broad ESW of aqueous electrolytes and high operating voltage in ZIBs, including the optimization of pH, utilization of bication electrolytes, introduction of small-dipole additives, and design of polymer-supported gel electrolytes.…”
Section: Electrolyte Modification For High Voltage Zinc-ion Batteriesmentioning
confidence: 99%
See 3 more Smart Citations
“…[27][28][29] Table 1 shows the reported electrolyte designs to improve the narrow ESW of aqueous electrolytes. [30][31][32][33][34][35][36][37][38][39][40][41] Herein, we discuss strategies to suppress water decomposition for the broad ESW of aqueous electrolytes and high operating voltage in ZIBs, including the optimization of pH, utilization of bication electrolytes, introduction of small-dipole additives, and design of polymer-supported gel electrolytes.…”
Section: Electrolyte Modification For High Voltage Zinc-ion Batteriesmentioning
confidence: 99%
“…For instance, Zafar et al developed a high-voltage aqueous Zn j graphite DIB based on an 8 m Zn(ClO 4 ) 2 WIS electrolyte. [37] They manipulated graphite as a cathode material and con- ducted cyclic voltammetry to determine the working potential (Figure 5b). The fabricated cell exhibited an oxidation peak (I pa ) at 2.4 V representing the ClO 4…”
Section: Energy Storage Via Anion Intercalationmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, electrochemical (de)lithiation of conventional active materials for both the anode and cathode of lithium ion batteries are allowed in WiSE, and the corresponding electrochemical potentials are beyond the limit of typical aqueous electrolyte solutions. [17][18][19][20][21][22][23][24][25][26][27][28][29][30] In addition to the interesting physicochemical characteristics of a bulk WiSE, an interfacial layer (IFL) on an electrode in WiSE was revealed to be distinctive compared to interfaces observed in conventional aqueous solutions with relatively low electrolyte concentrations (i.e., "salt-in-water" electrolyte solution). [31][32][33] Borodin et al reported that IFLs are strongly related to an applied electrode potential, referring to the point of zero charges (PZC) of an electrode.…”
Section: Introductionmentioning
confidence: 99%